Análisis discriminante descriptivo: teoría, algoritmo y software - Castillo Elizondo, William (1999)
The objetive of this article is to present a computational implementation of the Descriptive Discriminant Analysis. We have developed some theoretical aspects in order to formulate an algorithm that was implemented using C+ +. Finally, the method and the software are illustrated an example.